Noise level in a common area at a higher education institution in Uberaba/MG (International Seven Journal of Health Research, 2024)
Currently, noise pollution is the third main form of pollution and stands out as one of the main causes of deterioration in quality of life. For this reason, the aim was to explore the noise levels present in the common area of a Federal University and compare the results with reference values. The pressure levels in the canteen at the Federal University of Triângulo Mineiro are well above those established by the Brazilian Association of Technical Standards. Most of the noise intensity comes mainly from students and staff. Therefore, it is recommended to implement an awareness campaign aimed at this audience, aiming for collective well-being.